The effects of urolithin A on poly I:C-induced microglial activation - Mingo, Yakum Benard; Gabele, Lea; Lonnemann, Niklas; Brône, Bert; Korte, Martin; Hosseini, Shirin (Frontiers in Cellular Neuroscience, 2024)
Neuroinflammation can be triggered by various stimuli, including viral infections. Viruses can directly invade the brain and infect neuronal cells or indirectly trigger a "cytokine storm" in the periphery that eventually leads to microglial activation in the brain. While this initial activation of microglial cells is important for viral clearance, chronic activation leads to excessive inflammation and oxidative stress, which can be neurotoxic. Remarkebly, recent studies have shown that certain viruses such as influenza A virus, coronavirus, herpes virus and Epstein-Barr virus may be involved in the development of neurodegenerative diseases such as Parkinson's disease, Alzheimer's disease, and multiple sclerosis. Therefore, it is important to find therapeutic strategies against chronic neuroinflammation triggered by viral infections. Here, we investigated the effects of urolithin A (UA) on microglial activation in vitro induced by a viral mimetic, poly I:C, in a triple co-culture system of neurons, astrocytes and microglial cells. Immunocytochemistry was used to perform a comprehensive single-cell analysis of the morphological changes of microglia as an indicator of their reactive state. Treatment with UA significantly prevented the poly I:C-induced reactive state of microglia, which was characterized by increased expression of the microglial activation markers CD68 and IBA-1. UA restored the poly I:Cinduced morphology by restoring microglial ramification. In addition, UA was able to reduce the release of the pro-inflammatory mediators CCL2, TNF-α, and IL-1β and showed a trend toward attenuation of cellular ROS production in poly I:C-treated cultures. Overall, this study suggests that UA as a component of a healthy diet may help prevent virus-induced neuroinflammation and may have therapeutic potential for future studies to prevent or treat neurodegenerative diseases by targeting the associated neuroinflammatory processes.